Study of Hierarchy and Service Facility Centers of South Labuhanbatu Regency - Darwin Parlaungan Lubis; Sendi Permana; Muhammad Taufik Rahmadi; Mahara Sintong; Benedictus P Turnip (Universitas Lambung Mangkurat, 2023)
The regional hierarchy, which includes the functions targeted at each region, is an important consideration in regional planning. The implementation of this function is related to existing service facilities in each sub-district in terms of the growth dynamics of South Labuhanbatu Regency. The distribution of the population in the sub-districts of South Labuhantu Regency has resulted in an increase in the quantity of infrastructure, facilities and service facilities. This research was conducted to determine the availability of service facilities in Labuhanbatu District and to examine the hierarchy and distribution of service centers. This research uses a quantitative descriptive research method using the centrality index analysis method, gravity analysis, and nearest neighbor analysis. Based on the study findings, it is known that the availability of service facilities in Labuhanbatu Regency is quite adequate, especially considering that Kota Pinang and Torgamba Subdistricts which have first order status already have quite complete and adequate facilities. In addition to the findings of the regional hierarchy analysis based on analysis of the centrality and gravity indices, the findings of the nearest neighbor analysis also show Kota Pinang and Torgamba Districts in the hierarchy. Service centers in Labuhanbatu Selatan Regency are located in Kota Pinang Subdistrict, which is the capital of the subdistrict, and Torgamba Subdistrict, which has the most availability of facilities and is supported by a large population and strong interaction strength.